Managing Episodic Volunteers in Free/Libre/Open Source Software Communities - Barcomb, Ann; Stol, Klaas-Jan; Fitzgerald, Brian; Riehle, Dirk (IEEE Transactions on Software Engineering, 2022)
We draw on the concept of episodic volunteering (EV) from the general volunteering literature to identify practices for managing EV in free/libre/open source software (FLOSS) communities. Infrequent but ongoing participation is widespread, but the practices that community managers are using to manage EV, and their concerns about EV, have not been previously documented. We conducted a policy Delphi study involving 24 FLOSS community managers from 22 different communities. Our panel identified 16 concerns related to managing EV in FLOSS, which we ranked by prevalence. We also describe 65 practices for managing EV in FLOSS. Almost three-quarters of these practices are used by at least three community managers. We report these practices using a systematic presentation that includes context, relationships between practices, and concerns that they address. These findings provide a coherent framework that can help FLOSS community managers to better manage episodic contributors
Keywords: best practices; community management; episodic volunteering; free software; open source software